EVALUTION OF FUNGICIDES AGAINST RHIZOPUS FRUIT ROT OF TOMATO (Journal of Plant Disease Sciences, 2017)
Seven systemic and non-systemic fungicides were screened at different  concentrations (100, 500, 1000 & 2000 ppm) and to test their efficacy in vitro in vivo against Rhizopus Rot of tomato fungitoxicity test indicated that the . In vitro benomyl, Carbendzim12% +Mancozeb 63% (75 WP), Trifloxystrobin25% +  tebuconazole 50% (75 WG) and thiophanate methyl 70 WP at different  concentrations (100, 500, 1000 & 2000 ppm) were highly effective and resulted in  complete mycelial growth inhibition of . The lowest Rhizopus rot Rhizopus oryzae severity was observed in fruits treated with benomyl at 100 & 500 ppm,  trifloxystrobin (25%) + tebuconazole (50%) at 1000 and 2000 ppm concentration  followed by carbendazim (12%) + mancozeb (63%) (6.21 & 0.45 and 7.49 & 7.49  %) at 500 and 1000 ppm both in Pre- and Post-inoculation at 5 day after th inoculation, respectively. Carbendazim (61.11 & 24.99 % and 51.48 & 49.54 %)  found least effective against Rhizopus rot at 100 and 500 ppm on 5th day after  inoculation.
Keywords: Fruit Rot, Fungicides, Rhizopus oryzae In vitro In vivo